Tracing industrial sulfur contributions to atmospheric sulfate deposition in the Athabasca oil sands region, Alberta, Canada - Proemse, Bernadette; Mayer, B.; Fenn, M. (Pergamon, 2012)
Anthropogenic S emissions in the Athabasca oil sands region (AOSR) in Alberta, Canada, affect SO4 deposition in close vicinity of industrial emitters. Between May 2008 and May 2009, SO4-S deposition was monitored using open field bulk collectors at 15 sites and throughfall collectors at 14 sites at distances between 3 and 113 km from one of the major emission stacks in the AOSR. At forested plots >90 km from the operations, SO4 deposition was 1.4 kg SO4-S ha1 yr1 for bulk deposition and 3.3 kg SO4-S ha1 yr1 for throughfall deposition. Throughfall SO4 deposition rates in the AOSR exceeded bulk deposition rates atall sites by a factor of 2–3, indicating significant inputs of dry deposition especially under forest canopies. Both bulk and throughfall SO4 deposition rates were elevated within 29 km distance of the industrial operations with deposition rates as high as 11.7 kg SO4-S ha1 yr1 for bulk deposition and 39.2 kg SO4-S ha1 yr1 for throughfall at industrial sites. Sulfur isotope ratio measurements of atmospheric SO4 deposited in the AOSR revealed that at a few selected locations 34S-depleted SO4, likely derived from H2S emissions from tailing ponds contributes to local atmospheric SO4 deposition. In general, however, d34S values of SO4 deposition at distant forested plots (>74 km) with low deposition rates were not isotopically different from d34S values at sites with high deposition rates in the AOSR and are, therefore, not suitable to determine industrial S contributions. However, O isotope ratios of atmospheric SO4 in bulkand throughfall deposition in the AOSR showed a distinct trend of decreasing d18O-SO4 values with increasing SO4 deposition rates allowing quantification of industrial contributions to atmospheric SO4 deposition. Two-end-member mixing calculations revealed that open field bulk SO4 deposition especially at industrial sites in close proximity (<29 km) to the operations is significantly (17–59%) affected by industrial S emissions and that throughfall generally contained 49–100% SO4 of industrial origin. Hence, it is suggested that d18O values of SO4 may constitute a suitable tracer for quantifying industrial contributions to atmospheric SO4 deposition in the AOSR.